2009
DOI: 10.5585/conssaude.v8i3.1706
|View full text |Cite
|
Sign up to set email alerts
|

Variables associated with bruxism in children and adolescents

Abstract: The aim of the study was to assess the variables associated with bruxism and its prevalence in school children and adolescents. A group of 680 school children of both genders aged 4 -16 years old was randomly selected. Data were gathered by clinical exam and questionnaires filled out by guardians. Statistical analyses were performed by Chi-square test, Odds Ratio and SPSS package. Some factors like heredity, respiratory problems, headaches, difficulty with falling asleep, sleep talking and the schoolchild’s di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Gonçalves ve ark., 4-16 yaş grubu çocuklar üzerinde yaptıkları çalışmalarında, ailelerinde bruksizm görülen çocuklarda yaklaşık 3 kat daha fazla bruksizm görülebildiğini bildirmişlerdir. 29 Kasımoğlu ve ark. da yapmış oldukları çalışmada, çocuklarda bruksizm varlığı ile anne veya babada bruksizm varlığı arasında istatistiksel olarak anlamlı bir ilişki bulunduğunu belirtmişlerdir.…”
Section: Discussionunclassified
“…Gonçalves ve ark., 4-16 yaş grubu çocuklar üzerinde yaptıkları çalışmalarında, ailelerinde bruksizm görülen çocuklarda yaklaşık 3 kat daha fazla bruksizm görülebildiğini bildirmişlerdir. 29 Kasımoğlu ve ark. da yapmış oldukları çalışmada, çocuklarda bruksizm varlığı ile anne veya babada bruksizm varlığı arasında istatistiksel olarak anlamlı bir ilişki bulunduğunu belirtmişlerdir.…”
Section: Discussionunclassified
“…Again, these findings are in line with the available literature supports. Goncalves et al found a prevalence twice greater of morning headaches in children and adolescents with SB (OR � 2.6) [18]. Also, Bortoletto et al asserted that children with SB have a greater risk of having primary headache [25].…”
Section: Discussionmentioning
confidence: 99%
“…According to Santos-Suosa et al, SB in individuals with difficulty in sleeping may be a possible result of a nervous system excitation response accompanied by body movements [ 7 ]. Furthermore, Goncalves et al in a cross-sectional study reported an association between SB and problems with falling asleep, with an OR of 4.1 [ 18 ]. Also, as reported above, a couple of systematic reviews supported this relation [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%